DETERMINATION OF OBESITY INCIDENCE IN STUDENTS OF THE FACULTY OF MEDICINE AND HEALTH SCIENCES, UNIVERSITY OF JAMBI - Ramadhan, Nouval (Jurnal Kesmas Prima Indonesia, 2025)
Obesity a condition of excessive body weight, is a major nutritional issue and a known risk factor for degenerative diseases. Based on the 2023 Indonesian Health Survey, the prevalence of obesity among adults over 18 years old reached 23.4%. A preliminary survey of 10 students at the Faculty of Medicine and Health Sciences, University of Jambi, found 3 students to be obese. This study aims to analyze the factors associated with obesity among students at the faculty. This quantitative study used an analytical design with a cross-sectional approach and involved 136 respondents selected through proportionate stratified random sampling. Data collection utilized instruments such as the Stunkard Figure Rating Scale, PSQI, IPAQ-SF, PSS, and FFQ, along with direct measurements of body weight and height. The study found that 21% of the students were obese. There were significant associations between obesity and sex (p=0.017), parental body shape (p=0.025), sleep quality (p=0.005), and physical activity (p=0.005). However, no significant association was found with stress (p=0.361), consumption of high-risk foods (p=0.277), or fruit and vegetable intake (p=0.070). Sleep quality was identified as the most dominant factor (Adj PR 12.788). Sex was a protective factor, while parental body shape, poor sleep quality, and low physical activity were risk factors for obesity. Keywords: Obesity, College Students, Parental Stature, Stress, Sleep Quality, Consumption Patterns